32. STUDIES ON THE ASPERGILLUS FR.: FRI. OF FRUCTUS MALI COLLECTED FROM THE TRADITIONAL MEDICINE STORES IN HANOI (Vietnam Journal of Community Medicine, 2024)
Objective: To determine the Aspergillus species contamination of Fructus Mali samples.Materials and Methods: Ten samples of Fructus Mali were collected from the traditional herbal stores in Hanoi for fungal analyses. For the mycological analyses of the Fructus Mali samples the direct plating technique and PDA medium were used. The taxonomic systems of fungi (Samson et al., 1995; Pitt & Hocking 2009) were followed for the observation and identification. The isolates were cultured on Czapek-Dox.Results: Six species of the genus Aspergillus Fr.: Fr. were collected: Aspergillus niger, Aspergillus flavus, A. parasiticus, A. fumigatus, A. aculeatus, A. tamarii.Conclusion: These results identify potential source of mycotoxins in Fructus Mali and allude to the need of good storage practices in order to protect consumers from the health threat posed by mycotoxin contamination.
Keywords: Aspergillus, A. niger, A. flavus, A. parasiticus, A. fumigatus, A. aculeatus, A. tamarii, Fructus Mali.